If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-50y-25=15y-6
We simplify the equation to the form, which is simple to understand
-50y-25=15y-6
We move all terms containing y to the left and all other terms to the right.
-50y-15y=-6+25
We simplify left and right side of the equation.
-65y=+19
We divide both sides of the equation by -65 to get y.
y=-0.292307692308
| 8.3x+55.58=11.7x+54.68 | | -8x+12=-8x+5 | | -2(x+4)+3y=-5x+y-6 | | 6x+12-12=-6x | | 0-a=-2 | | 0.5x^2+2.5x-1.5=0 | | 3x^2+3x=180 | | -3x+7y*0=-21 | | 6x+12=3x-1 | | x*12x=2 | | -3x*0+7y=-21 | | -5-(15y-1)=2(7y-16y)-y | | 7(b+2)-2(b+10)-4b=5 | | 106-2=7b-7.4 | | f/10+5.9=1.8 | | 6(6v+6)+5=1+6v | | 12m-9-4m=15 | | -5*0+10y=-50 | | 5p+3p-8=p-1 | | 7(m+4)=2m+20 | | -5*0+10=-50 | | 3/4+4x=3/4 | | 2(x+4)=4(x-6) | | 12ln(x)=-6 | | 12lnx=-6 | | 2=-1+k/4 | | 3ln(4x)=-6 | | Y-1=-2x-12 | | 5x-1(2x+14)=10 | | .08m=3 | | x+(x+1)=2+(x+3) | | 0=-9(2x-4) |